Developing Academic Writing Skills Among First-Year Students (Participatory Approach to Understanding Scientific Paper Standards in Higher Education) - Prasetiyo, Eko; Sholeh, Zain Zuhri (At Taawun Bangun Bangsa, 2025)
This study addresses the persistent challenge faced by first-year university students in understanding and applying academic writing conventions required in higher education. The research responds to the gap between students’ writing ability and the methodological and linguistic standards expected in academic contexts. The primary objective was to develop students’ competence in writing scientific papers that are logical, structured, and ethically sound. The program employed Participatory Action Research (PAR) combined with the Asset-Based Community Development (ABCD) approach, encouraging students to engage actively through experiential learning, reflection, and peer collaboration. Conducted over two days at the Institut Agama Islam (IAI) Ngawi, the training involved 150 participants, including PMII cadres and first-year students. Findings revealed significant improvement in participants’ understanding of academic paper structure, citation practices, and argument development. Moreover, participants demonstrated greater confidence and motivation to write scientific papers independently. The study concludes that participatory and asset-based learning strategies effectively transform academic writing from a procedural task into an intellectual and reflective process, fostering long-term academic literacy and integrity.